Nursing Care for Hyperthermia in Patient Nn. Y.T with Tropical Malaria in the Internal Ward Class III (PT. LARPA JAYA PUBLISHER, 2025)
Malaria is a mosquito-borne disease caused by obligate intracellular protozoa of the genus Plasmodium. It can affect individuals of all ages, particularly those living in areas suitable for mosquito breeding. This study employed a case study design involving one adult patient diagnosed with tropical malaria and experiencing hyperthermia. Data were collected through interviews, observation, and documentation, then analyzed using a systematic process of data collection, data reduction, data presentation, and conclusion drawing. Nursing care focused on managing hyperthermia through the application of warm compresses on affected areas, including the forehead, axilla, and groin. Following the intervention, the patient’s body temperature decreased from 38.2°C to within the normal range. The intervention also contributed to patient comfort, reduced chills, and improved peripheral circulation. These findings indicate that warm compresses are an effective non-pharmacological nursing intervention for reducing elevated body temperature in malaria patients, supporting thermoregulation, enhancing patient comfort, and complementing medical treatment. Implementing timely and appropriate nursing interventions can play a critical role in managing hyperthermia, minimizing complications, and promoting faster recovery in patients with malaria.